El impuesto predial y su impacto en los ingresos de la Municipalidad Distrital de Víctor Larco Herrera 2005-2010. - Massé Miguel, Paola Vanessa (2012)
The present paper has the goal of determining in which level the property tax has an impact on the income of Victor Larco Herrera Municipality in the province of Trujillo for the 2005-2010 period. This Municipality is a legal person of public law, capable of managing its own economical and financial resources in behalf of the development of the social community of its jurisdiction. According to its nature, the Municipality should comply the double function of government and services manager; being able to generate and manage its own tax resources and municipal income. This is the reason why the property tax shows an incidence in the incomes. By means of the present paper it is intended to study and analyse the structure of the incomes of the Victor Larco Herrera Municipality and quantify the impact of the property tax in this tax structure, as well as analysing the property tax with and without arrears on the total incomes in order to determine its grade of incidence Based on what has been exposed, the respective conclusions and recommendations have been elaborated in order to improve the effective collection of property tax in the Victor Larco Herrera Municipality.